2010
DOI: 10.12693/aphyspola.117.706
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Social Systems

Abstract: The term "complexity" used frequently as a kind of "buzzword" has gained a specific role in the language of modern social sciences and social practice. A question is arising -how can we understand complexity of social systems/social phenomena which are characterized by limited possibility of explanation, unpredictability or low reliability of prediction? The aim of the paper is to provide a partial answer to this question. A survey of characteristics of complex systems and typology of various kinds of complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
0
10
0
8
Order By: Relevance
“…The intricacy of complexity studies can be found in the scheme proposed by Castellani [2018]. In other writings several definitions of complexity have been formulated and scrutinized - [Weaver 1948;Prigogine, Stengers 1984;Waldrop 1992;Gell-Mann 1995;Kauffman 1995;Bar-Yam 1997;Biggiero 2001;Andriani, McKelvey 2009;Mesjasz 2010]. The unequivocal distinction of complex systems from the "classical" systems is not possible.…”
Section: "Hard" and "Soft" Complexity Of Social Systemsmentioning
confidence: 99%
“…The intricacy of complexity studies can be found in the scheme proposed by Castellani [2018]. In other writings several definitions of complexity have been formulated and scrutinized - [Weaver 1948;Prigogine, Stengers 1984;Waldrop 1992;Gell-Mann 1995;Kauffman 1995;Bar-Yam 1997;Biggiero 2001;Andriani, McKelvey 2009;Mesjasz 2010]. The unequivocal distinction of complex systems from the "classical" systems is not possible.…”
Section: "Hard" and "Soft" Complexity Of Social Systemsmentioning
confidence: 99%
“…W konsekwencji, dynamika nieliniowa powoduje, iż przebieg zjawisk staje się nieprzewidywalny. Jest tak dlatego, że może konstytuować się wiele trajektorii i wyłonić się wiele atraktorów [Mesjasz 2010]. Dynamika zjawisk może również charakteryzować się tym, że niewielkie zakłócenia mogą prowadzić do zmian podobnych do lawin (avalanches) o najróżniejszych rozmiarach.…”
Section: Destabilizacja I Złożonośćunclassified
“…Odzwierciedla to szereg definicyjnych ujęć wzmiankowanego terminu [Mesjasz 2010]. W kontekście badań nad organizacjami wydaje się, że zasadne jest przyjęcie założenia zarów-no o stopniu skomplikowania problemów, jak i kompleksowości.…”
Section: Ontologiczne I Epistemologiczne I Uwarunkowania Złożonościunclassified